INDIGENOUS COUNSELING: KARAKTERISTIK SPIRITUAL DALAM TRADISI ROBO-ROBO PADA MASYARAKAT KECAMATAN SUNGAI KAKAP, KALIMANTAN BARAT - Saripaini, Saripaini (Jurnal Studi Agama dan Masyarakat, 2021)
The robo-robo tradition is a traditional ritual carried out by the Sungai Kakap people as an effort to resist danger. This study explored to describe and identify the characteristics of people spirituality in the process of providing assistance through local community traditions. This research was a qualitative research using descriptive method. Data was collected by observing people